Fabrication of tin nanoparticles with functionalized platinum nanodendrites on ITO electrode for simultaneous detection of Cd2+, Pb2+, and Cu2+ ions - Nurul Hidayah Ramli; Noorhashimah Mohamad Nor; Zainovia Lockman; Khairunisak Abdul Razak (Results in Chemistry)
Heavy metals have high density and are toxic even at low concentrations (ppb). The industrial discharge of heavy metals led to the accumulation in food chains, causing significant risks to human health and the environment. The detection of heavy metals is crucial for monitoring heavy metal contamination. Tin nanoparticles (SnNPs) have low toxicity, are inexpensive, have good conductivity and can be used to modify electrodes for heavy metal detection. However, electrochemical sensors using SnNPs suffer from a lack of sensitivity. To address this issue, platinum nanodendrites (PtNDs) were used with SnNPs for modification with an indium tin oxide (ITO) electrode to enhance the sensitivity of the modified electrode. PtNDs were surface functionalized with citric acid (CA) and 2-[methoxy-(polyethyleneoxy)propyl] trimethoxysilane (PEG) to improve the stability of the colloidal PtNDs. Nafion was added as the outer layer of the modified electrode to improve and stabilize the modified electrode. The produced electrode was subjected to cyclic voltammetry (CV) in 5.0 × 10−3 mol/L potassium ferrocyanide, [Fe (CN)6]3−, in a 0.1 mol/L KCl solution (pH 7.0) and square wave anodic stripping voltammetry (SWASV) in 0.2 M acetate buffer solution (pH 4.5). The optimized electrode, namely, Nafion/7 µL PtND-CA-SnNP/ITO, demonstrated high sensitivity and selectivity and successfully detected Cd(II), Pb(II), and Cu(II) ions during simultaneous detection with linear ranges of 1–5 ppb for low concentration and 10–100 ppb for high concentration. The limits of detection (LOD) for Cd(II), Pb(II), and Cu(II) ions were 1.50, 2.0, and 1.89 ppb, respectively. The modified electrode exhibited remarkable sensitivity to these ions: 1.09 µA/ppb for Cd(II), 2.5 µA/ppb for Pb(II), and 0.96 µA/ppb for Cu(II). The interference study revealed that the modified electrode had high selectivity toward Cd(II), Pb(II), and Cu(II) ions. The applicability of the Nafion/7 µL PtND-CA-SnNP/ITO-modified electrode was tested in seawater for heavy metal detection. The successful detection of Cd(II), Pb(II), and Cu(II) ions in seawater samples demonstrated the modified electrode’s potential for use in heavy metal sensors.